Knowledge, attitude, practice and associated factors about voluntary blood donation among regular undergraduate students of Wachemo University, Southcentral Ethiopia: a cross-sectional study - Mussema, Abdulhakim; Nigussie, Bethelhem; Anmaw, Biruk; Abera, Habtamu; Nageso, Habib; Gebre Bawore, Solomon; Shemsu, Amina; Woldesenbet, Dagmawi; Mohammed, Kemal; Seid, Abdurezak Mohammed; Admasu, Dawit (Frontiers in Public Health, 2024)
IntroductionHuman blood plays a crucial role in transporting metabolic waste and essential minerals, including oxygen, to cells. Blood transfusions are a critical intervention in various situations such as trauma, inherited bleeding disorders, childbirth, and numerous medical and surgical procedures, often being the only means to prevent death. A significant challenge, particularly in developing nations, is maintaining a sufficient supply of safe blood. An individual’s mindset, beliefs, and familiarity with blood donation significantly affect their willingness to donate. This research aimed to evaluate the knowledge, attitudes, practices, and related factors concerning voluntary blood donation among undergraduate regular students at Wachemo University in Southcentral Ethiopia.Materials and methodsA cross-sectional study was conducted from October 19 to November 10, 2023, using a stratified random sampling method to select participants. Data were gathered through self-administered structured and semi-structured questionnaires. The responses regarding knowledge, attitudes, and practices were analyzed using SPSS version 24 and presented through text, figures, and tables.ResultA total of 393 respondents participated in the study (97.76% response rate), comprising 59% males and 41% females. Of the participants, 77.6% demonstrated adequate knowledge, 79.6% exhibited positive attitudes, while only 19.3% had engaged in blood donation. Factors influencing these outcomes included knowledge, previous residence, and college background. Reluctance to donate blood was primarily linked to fear and concerns about time constraint.Conclusion and recommendationsThe findings indicate that while a majority of students possess good knowledge (77.6%) and favorable attitudes (79.6%) toward blood donation, only a small fraction (19.3%) actively participates in the practice. It is recommended that the institution collaborate with relevant stakeholders to address the factors affecting voluntary blood donation among students. In addition, incorporating topics on blood donation and its significance into the university curriculum can foster a culture of generosity among students. This strategy is essential for improving blood donation rates in this region.